SPEAKING ANXIETY AMONG B1 LEVEL STUDENTS IN ENGLISH CLASSROOM - Azadova Shaxina Sherzodovna; Mirkomilova Mohlaroy Baxtiyorovna (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
Speaking anxiety is a common problem faced by English learners, especially B1 level students. This article examines the impact of speaking anxiety on lesson effectiveness and students’ participation in English classes. It also identifies the main causes, such as fear of making mistakes and lack of confidence, and explores effective methods to help reduce anxiety and improve students’ speaking performance.